Children's Views on Their Lives and Well-being : Findings from the Children's Worlds Project - Rees, Gwyther (Springer International Publishing : Imprint: Springer, 2017)
This book presents a comprehensive overview of findings from the Children's Worlds project - the most extensive and diverse study to have been conducted globally on children's own views of their lives. It provides a unique comparative insight into the similarities and differences in children's lives and well-being around the world, including findings that challenge prevailing assumptions of where, and in what contexts, children might experience a 'good childhood'. The book draws out the key messages and implications from the study and identifies directions for future work on child well-being. It will be of interest to researchers and students in the field of childhood studies, as well as a wide range of professionals and organisations concerned with improving children's quality of life.
Keywords: Social sciences.; Well-being.; Children.; Social justice.; Human rights.; Positive psychology.; elektronické knihy; electronic books